Cores of composite structures made of semi-rigid foams for use as protecting shields for firefighters - Ryszkowska, J.; Szczepkowski, L.; Aleksandrowicz, J.; Wierzbicki, Ł.; Kukfisz, B.; Półka, M.; Bryśkiewicz, A.; Auguścik, M.; Leszczyńska, M.; Oliwa, R. (Polimery, 2021)
The subject of the paper are semi-rigid polyurethane foams. They belong to a group of energy-absorbing materials, which have been used for manufacture of structural components of protecting shields for firefighters. In order to increase the fire resistance of the foams they were modified by addition of expandable graphite and Fyrol PNX. As a result, flame retardant foams have been obtained, with reduced flammability and limited amount of smoke emission, having an ability to absorb impact energy in the amount of 12–19 %. By introducing a rubber waste during the manufacture of foam composition, the price of foams was reduced by about 25 %.